INTEGRASI NILAI- NILAI KARAKTER DALAM PROSES PEMBELAJARAN - Khoeriyyah, Ahliyatul; Tri Lestari, Nur Citra; Gustiani Sadisatul Mu’akhiroh; Zhafirah Aldini, Shalfa; Khobir, Abdul; Kamilia, Nadya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The integration of character values into the learning process is an urgent necessity amid the increasing phenomenon of moral degradation among students. This article aims to examine the concepts, strategies, and implementation of character value integration in learning activities across various levels of education. The study employs a library research method with a qualitative descriptive approach through the analysis of scientific journals, books, and relevant educational policy documents published between 2018 and 2025. The findings indicate that the integration of character values including honesty, responsibility, discipline, cooperation, and tolerance can be effectively achieved through three main strategies: (1) explicit embedding of values in character-based teaching materials, (2) application of active and contextual learning methods grounded in local wisdom, and (3) holistic evaluation encompassing affective aspects in a formative and ongoing manner. The Character Education Strengthening Policy (PPK) and the Merdeka Curriculum provide a strong normative foundation; however, implementation remains constrained by insufficient teacher understanding, limited parental support, and the influence of global culture. This article affirms that the integration of character values is not merely a curricular addition, but the very essence of the entire learning process that educators must consistently and sustainably embody. Strong synergy among schools, families, and communities, along with systematic strengthening of teachers' professional capacity, is essential to ensure character education is genuinely internalized in students' daily lives.